Meniscal Scaffolds - Myers, Kevin R.; Sgaglione, Nicholas A.; Goodwillie, Andrew D. (The Journal of Knee Surgery, 2014)
There are two scaffold products designed for meniscal reconstruction or substitution of partial meniscal defects that are currently available in the Europe: the collagen meniscal implant (CMI; Ivy Sports Medicine, Gräfelfing, Germany) and the polymer scaffold (PS; Actifit, Orteq Bioengineering, London, United Kingdom). The CMI has demonstrated improved clinical outcomes compared with baseline in patients with chronic postmeniscectomy symptoms with follow-up ranging from 5 to more than 10 years. There are also several comparative studies that report improved clinical scores in patients with chronic medial meniscus symptoms treated with CMI versus repeat partial meniscectomy, and a lower reoperation rate. Recently, PS insertion was shown to result in improved clinical outcomes in patients with chronic postmeniscectomy symptoms of the medial or lateral meniscus at short-term follow-up. However, there is currently no medium- or long-term data available for the PS. The use of meniscal scaffolds in the acute setting has not been found to result in improved outcomes in most studies. The authors' surgical indications for meniscal scaffold implantation, preferred surgical technique, and postoperative rehabilitation protocol are described.
Keywords: meniscal scaffold; meniscal substitution; partial meniscectomy